2014
DOI: 10.1073/pnas.1410609111
|View full text |Cite
|
Sign up to set email alerts
|

TAp73 opposes tumor angiogenesis by promoting hypoxia-inducible factor 1α degradation

Abstract: Tumor hypoxia and hypoxia-inducible factor 1 (HIF-1) activation are associated with cancer progression. Here, we demonstrate that the transcription factor TAp73 opposes HIF-1 activity through a nontranscriptional mechanism, thus affecting tumor angiogenesis. TAp73-deficient mice have an increased incidence of spontaneous and chemically induced tumors that also display enhanced vascularization. Mechanistically, TAp73 interacts with the regulatory subunit (α) of HIF-1 and recruits mouse double minute 2 homolog i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 29 publications
1
102
0
2
Order By: Relevance
“…Transient overexpression of TAp73 leads to pro-angiogenesis. In contrast, long-term induction of TAp73 leads to angiogenic suppression (26). Similarly, we also found TAp73 could inhibit the ability of tube formation in human umbilical vein endothelial cells (HUVEC) when HUVEC co-cultured with H1299 LAC cells with TAp73 stable overexpressed not for transient transfection (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Transient overexpression of TAp73 leads to pro-angiogenesis. In contrast, long-term induction of TAp73 leads to angiogenic suppression (26). Similarly, we also found TAp73 could inhibit the ability of tube formation in human umbilical vein endothelial cells (HUVEC) when HUVEC co-cultured with H1299 LAC cells with TAp73 stable overexpressed not for transient transfection (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…For example, the involvement of the prolyl hydroxylase (PHD) enzyme, which induce hydroxylation of proline residues under normoxia, as well as the von Hippel-Lindau (VHL) protein, which recognize hydroxylated prolines and induce the poly-ubiquitination to mediate proteasomal HIF degradation, need to be analyzed for a full overview of the pathway 29,30 . Moreover, ubiquitous detection of HIFs would also determine the protein stability and degradation that can be alter 31,32 . Furthermore, proliferation by Ki67 and apoptosis by TUNEL staining are determined in vivo through staining of AT histological sections.…”
Section: Representative Resultsmentioning
confidence: 99%
“…We demonstrated that the p53-like responsive element in the BNIP3 promoter, previously experimentally validated for p53 can also be recognized by TAp73. As BNIP3 is a HIF1a target gene, 90 and HIF1a is repressed by TAp73, 41 relationship between TAp73 and BNIP3 can also depend on an indirect regulation via HIF1.…”
Section: Discussionmentioning
confidence: 99%
“…TAp73 indeed directly binds HIF-1a protein, promoting its oxygen-independent degradation. 41,42 Conversely, DNp73 antagonizes TAp73 and it is considered an oncogenic protein. [43][44][45][46] It can form inactive complexes with TAp73, and also bind common promoters with p53 and TAp73, thus inhibiting their transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%